Responsibilities for harm reduction and prevention in online gambling: Evidence from newly regulated license-based markets - Marionneau, Virve; Kivistö, Mette; Karlsson, Nina (Critical Gambling Studies)

(untitled) (University of Alberta Library, 2025)
Gambling harm prevention and reduction consists of a range of upstream and downstream solutions. Responsibilities for implementing and ensuring these tasks falls across a range of actors, including policymakers, regulators, health professionals and industry. Increased harms caused by online gambling necessitate new regulatory measures, and potentially new responsibilities for their implementation. The current study uses key informant interview data (N=10) conducted in four jurisdictions that have recently introduced a license-based online gambling market (Germany, the Netherlands, Sweden, Ontario). Our aim was to identify what kind of responsibilities for harm prevention and reduction emerge in competitive online markets, to whom responsibility for these tasks is assigned, and what kind of barriers to harm prevention exist across responsibilities. Our analysis shows that most universal responsibilities are assigned to policy makers and regulators. Selective measures aiming at those who gamble, are largely implemented in collaboration between regulators and industry. Indicated and treatment-focused measures are the shared responsibility of treatment professionals, regulators and industry. The main barriers to effective harm prevention related to conflicting interests, industry power, lacking harm prevention resources, lacking centralisation and offshore provision. We argue that improved harm prevention would require balancing existing asymmetries that relate to power, responsibilities and prioritisations.